Pengaruh Senam Disminore Terhadap Penurunan Nyeri Disminore Pada Remaja Putri - Ana Mariza; Asni Lazary (Universitas Malahayati Lampung, 2022)
ABSTRACT Dysmenorrhoea is a menstrual disorder with the greatest prevalence that adolescents often complain of as an uncomfortable sensation, this characteristic of pain is very typical because it appears regularly and periodically accompanies menstruation. In order to reduce sensory neri, it can be overcome by two types of therapy, namely pharmacology and non-pharmacology, one of them with disminore exercise. The purpose of this study was to determine the effect of disminore gymnastics on the reduction of disminore pain in young women in Seputih Surabaya 1 State Senior High School. This type of pre-experimental research uses the design of One Group Pretest Posttest Design. The population is all young women who have disminore pain complaints. The sample is determined by purposive sampling technique based on the inclusion and exclusion criteria obtained by the number of samples as many as 20 respondents. The research instrument is a pain scale observation sheet. The statistical test used was the Wilcoxon Signed Ranks Test with a significance level of 0.05. The results of the study of pain scale distribution in young women before exercising disminore in the medium category were 55% with an average value was 4.95 and a standard deviation = 1,276. Pain scale distribution after doing disminore exercise in the medium category is 65% with an average value is 3.90 and the standard deviation = 0.912. There is an effect of disminore gymnastics on decreasing disminore pain in young women with p value = 0,000. Conclusion there is the influence of disminore gymnastics on the reduction of disminore pain in young women in Seputih Surabaya State 1 Central Lampung District, so that it can be suggested that health workers, especially midwives, do health promotion to young women about disminore gymnastics by coordinating with the school as an alternative reduce pain. Keywords: Disminore gymnastics, Disminore pain, Menstruation ABSTRAK Dismenorea merupakan gangguan menstruasi dengan prevalensi terbesar yang sering dikeluhkan remaja sebagai sensasi tidak nyaman, karakteristik nyeri ini sangat khas karena muncul secara reguler dan periodik menyertai menstruasi. Guna mengurangi sensani neri tersebut dapat diatasi dengan dua jenis terapi yaitu farmakologi dan non farmakologi salah satunya dengan senam disminore. Tujuan dari peneltiian ini untuk mengetahui pengaruh senam disminore terhadap penurunan nyeri disminore pada remaja putri di SMA Negeri 1 Seputih Surabaya Kabupaten Lampung Tenga. Jenis penelitian pre eksperimen menggunakan rancangan One Group Pretest Posttest Design. Populasi adalah keseluruhan remaja putri yang mempunyai keluhan nyeri disminore. Sampel ditentukan dengan tehnik purposive sampling berdasarakan kriteria inklusi dan eksklusi diperoleh jumlah sampel sebanyak 20 responden. Instrumen penelitian adalah lembar observasi skala nyeri. Uji statistik yang digunakan adalah uji Wilcoxon Signed Ranks Test dengan tingkat kemaknaan 0,05. Hasil penelitian distribusi skala nyeri pada remaja putri sebelum melakukan senam disminore dalam kategori sedang sebanyak 55% dengan nilai rata-rata adalah 4,95 dan standar deviasi = 1,276. Distribusi skala nyeri sesudah melakukan senam disminore dalam kategori sedang sebanyak 65% dengan nilai rata-rata adalah 3,90 dan standar deviasi = 0,912. Terdapat pengaruh senam disminore terhadap penurunan nyeri disminore pada remaja putri dengan nilai p value = 0,000. Kesimpulan terdapat pengaruh senam disminore terhadap penurunan nyeri disminore pada remaja putri di SMA Negeri 1 Seputih Surabaya Kabupaten Lampung Tengah. Disarankan agar para tenaga kesehatan khususnya bidan untuk melakukan promosi kesehatan kepada remaja putri mengenai senam disminore dengan berkoordinasi dengan pihak sekolah sebagai alternatif menurunkan nyeri. Kata Kunci: Senam Disminore, Disminore, Menstruasi